Audit of Emergency Obstetric Referrals- A Pilot Study From Tertiary Care Centre of North India (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s):The aim of the study was to find out the characteristics of emergency obstetric referrals, to evaluate the lapses in the existing referral system and to suggest the plausible solutions to improve the obstetric health care delivery system in India.Materials and methods: This prospective descriptive study was carried out in the Department of Obstertrics and Gynaecology PGIMER Chandigarh India from September 2012 to December 2012.All the obstetric emergency referrals to our institute, a tertiary care centre in North India were critically reviewed for reason for referral, adequacy of care provided before referral, lapses in management, factors behind suboptimal care and remedial measures are suggested.Results: There were 232 emergency referrals available for analysis. Of these 76% patients were referred directly to the institute, the highest level in referral chain in the region. Mean age was 26yrs, 28.6% of the patients were illiterate. In 75.5% of cases, the management of obstetric emergency before referral was suboptimal or poor. In 16% of cases patient failed to seek medical help timely despite emergency. In 40% of cases there was undue delay in referring or failure to provide even the basic care. Anticipated premature delivery and hypertensive disorders of pregnancy were the most common diagnosis at referral.Conclusion: Results from this pilot study shows that in spite of the most extensive health care infrastructure and so- called hierarchal referral system, there is gross inadequacy in referral system in India.Bangladesh J Obstet Gynaecol, 2015; Vol. 30(1) : 25-29